(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the sleep quality of students at Thang Long University. Subject and method: A cross-sectional descriptive study using the PSQI scale was conducted on 602 students across all majors. Results: The proportion of students with poor sleep quality was 61.5%. Sleep quality according to students’ subjective feelings: very good is 12.3%, fairly good is 60.5%, quite bad is 24.1%. Conclusion: The rate of students with poor sleep quality is still quite high, so appropriate solutions are needed to improve this situation.